Comparison of oxygen saturation range on the basis of mode of delivery in term new-borns: an observational study - Gautam, Shweta; Eske, Gunvant Singh; Agrawal, Avyact (International Journal of Contemporary Pediatrics, 2018)
Background: All newborns are cyanotic immediately after birth. Gradually within next few minutes of life this saturation increases and reaches target level in approximately 10 minutes. But the saturation range differs on the basis of amount of stress a neonate develops while being delivered out of mother’s womb. Methods: A total of 215 term healthy neonates were included out of which 131 were delivered vaginally and 84 were delivered via cesarean section (elective or emergency). Relevant antenatal history was taken and noted. Pulse oximetry readings were recorded continuously by using Masimo rad 5 pulse oximeter with signal extraction technology (SET) for first 10 minutes of life in all neonates. Results: At 1min of life spo2 of vaginal delivered babies was 70%(66% -73%) compared to cesarean delivered babies being 62%(57%-69%) with a highly significant p value (<0.001). Similarly, at 5 min the SpO2 was 89 % (85%-91%) and 80% (78%-82%) in normal vaginal delivered and cesarean section babies respectively. At 10 min of life when SpO2 measured in both groups the saturation difference was less but still significant. Conclusions: all neonates at birth are cyanotic and have a lower saturation which increases gradually with time. Ceserian delivered neonates have a low saturation range as compared to vaginal delivered newborn.